Geology of India - Ramakrishnan, M; Vaidyanadhan, R (Bangalore : Geological society of India, 2010)
The present two volumes provide an exhaustive and commendable synthesis of Indian geology, covering major recent advances. The editors have thereby generated, perhaps, the most up-to-date and authentic publication on the subject now available. The authors have taken to a central path in areas of modeling diversity. Most evolutionary models find a mention in the text. Areas of geophysics and geochemistry are emphasized, but the main focus is on structure, tectonics, stratigraphy and the geological milieu. Though the global stratigraphic scale is broadly followed, formations are described keeping in view their spatial and temporal continuity. Such a presentation has the merit of ensuring a wholesome picture of the geological history behind each of these geological entities which will be lost when forced into the various systems in the international scale. Geology of India presents a selected bibliography that lists most of the significant contributions. The authors are constrained to be brief in several sections due to limitations of space. A comprehensive treatise, Geology of India would prove to be an up-to-date source of information on Indian continental geology.
Includes Bibliography 521-549p.; Index 550-556p.
Keywords: Geology of India; Geology